Impact evaluation of community management of rice-fish system in Assam - Baruah, Uttam Kumar; Talukdar, Rajendra K; Goswami, Umesh C; Bhagowati, Ajit Kumar (Indian Journal of Fisheries, 2011)
The present study deals with the community management of rice-fish systemin an area of 66.8 ha at a remote village of Jhuria, Nagaon, Assam. The studyreveals the farmers' positive attitude towards the efficacy of collective actionin management of rice - flood, and a change in the concept of access to resourceby right. The farmers realised the benefits of managing the rice-fish systemcollectively rather than individually. They obtained a yield of 2,100-2,300 kgof rice grain per ha and 400-450 kg fish per ha and around 30,000 carried overfish seed. The fish yield was equivalent to 2,209 kg rice grain per ha. Theexperience resulted in more favourable attitude towards common managementof rice-flood, increased satisfaction with fish yield and the development of astrong sense of belonging to the group. More ponds were either dug or enlarged